High Fluid Velocity and Narrow Channels Enhance the Influences of Particle Shape on Colloid Retention in Saturated Groundwater Systems Under Favorable Deposition Conditions - Li, Ke; Ma, Huilian (Frontiers in Water, 2021)
Many particulate pollutants in the environment exist in non-spherical shape, but the influences of particle shape on pollutant migration and removal in groundwater systems are not well-understood. In this work, we simulated the three-dimensional translational and rotational motions of rod-shaped colloids in simple flow channels characterizing groundwater flow paths, with an aim to elucidate the underlying mechanisms for rod retention. Through an investigation of the interplay of multiple factors (e.g., aspect ratio, particle size/density, flow shear, channel dimension, and orientation relative to gravity), we determined under what conditions particle shape has the most pronounced impact on transport and retention under favorable deposition conditions (i.e., lacking repulsive energy barriers). Our results showed that in many cases, medium sized rods of ~0.4–2 μm in equivalent volume diameter exhibited much improved retention compared to equal-volume spheres, since for that size range, particle rotation from shape-induced fluid hydrodynamics and rotational diffusion were both important, which caused rods to drift considerably across flow streamlines to intercept collector surfaces. Particle rotation also allowed rods to travel farther downstream along flow channels for retention compared to spheres. The differences in retention between rods and spheres were more evident at relatively high fluid velocity, narrow flow channel, or when flow direction aligned with gravity. Our findings demonstrated that the effect of particle shape on pollutant transport and migration in groundwater systems was essential and provided important guidelines in optimizing parameter designs to utilize particle shape effect for better pollutant removal.